Tinker, Tiller, Technical Change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
case studies will form a major new book in 1990 from IT Publications, called 'Tinker Tiller, Technical Change'